Escorpiões do complexo Tityus stigmurus (Buthidae): delimitação de espécies e relação com bactérias do gênero Wolbachia - Gracielle de Fátima Braga Pereira (2015)
The Tityus stigmurus complex receives great attention in the literature due to its medically importance scorpions. The group currently includes six species: Tityus aba, T. kuryi, T. martinpaechi, T. melici, T. serrulatus and T. stigmurus. However, the limits between species of the group are controversial. Morphological data, mostly from coloration and tegument granulation, have not been sufficient to define species within the group. The use of molecular data can contribute to resolve the complex internal classification. The fast-evolving mitochondrial DNA is an appropriate tool to study cryptic and recently diverging species, but it can be influenced by intracellular microorganisms in linkage disequilibrium. The intracellular bacteria Wolbachia was recently found in the yellow scorpion (T. serrulatus) and have been suggested as responsible for the parthenogenesis in this species. Additionally, this bacteria is known to cause selective sweep of mitotypes in parasitized populations. In this study I used the DNA amplification tests of the bacterial genes WSP and ftsZ to confirm the presence of Wolbachia in tissues of different populations of parthenogenetic T. serrulatus. This tested was also performed for T. serrulatus sexual populations, as well as for other species of the complex. All results were negative for Wolbachia, indicating that the infection by this bacteria is not the cause of parthenogenesis in this T. serrulatus. These results also allow the use of mitochondrial genes to reliably infer phylogenetic relationships within the complex, since its evolutionary histories are not affected by this bacteria. Hence I used the mitochondrial markers COI and 16S and the nuclear ITS2 to test hypotheses of species delimitation within the complex from topologies generated by Maximum Likelihood and Bayesian Inference. All analyses indicate that the complex is monophyletic. However, only T. kuryi and T. melici are recuperated as monophyletic. Deep coalescence analyses indicate the existence of three evolutionary lineages within the complex, two of them corresponding to those monophyletic species and a third including the remaining species of the complex. Based on these results, I discuss in this dissertation the phylogenetic relationships of the Tityus stigmurus complex, comparing molecular results with morphological data present in the literature and observed during this study.